Investigating the relationship between cycle threshold of SARS-CoV-2 RT-PCR, clinical features, and laboratory data in hospitalized COVID-19 patients in Semnan, Iran - Kalantar Neyestanaki, Mohammad Hassan; Gholizadeh, Omid; Yasamineh, Saman; Tarahomi, Mahdieh; Pooya, Pegah; Eslami, Majid; Dadashpour, Mehdi; Ghaffari, Hadi (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCOVID-19, caused by the SARS-CoV-2 virus, has emerged as a global public health crisis. Understanding the factors associated with disease severity and outcomes is crucial for effective patient management. This study aimed to investigate the association between cycle threshold (CT) values, demographic data, medical history, clinical manifestations, and laboratory findings in hospitalized COVID-19 patients in Semnan, Iran.MethodsA cross-sectional study was conducted on 86 patients with confirmed COVID-19 admitted to two hospitals in Semnan, Iran, between December 2022 and March 2023. Respiratory swab samples were collected RT-PCR was performed, CT values were obtained, and data were collected from medical records, including demographic information, medical history, clinical manifestations, and laboratory results. Statistical analysis was performed using SPSS software.ResultsThe study included 86 COVID-19 patients, with a slightly higher representation of females (55.8%) and a mean age of 67.43 years. Pre-existing conditions like hypertension, diabetes mellitus, and ischemic heart disease were prevalent among hospitalized patients. A majority of patients (59.3%) had severe COVID-19, as indicated by lower CT values, while 31.4% exhibited oxygen saturation levels below 90%. Significant differences were observed in FBS, CRP, WBC, Hb, Cr, and SPo2 levels between severe and non-severe patients. Correlation analysis revealed associations between age, CRP, Cr, BUN, FBS, Vitamin D, TG, LDL, HDL, AST, ALP, and SPo2. Reflecting complex interactions between inflammatory markers, organ function, and lipid metabolism in COVID-19 patients.ConclusionThis study provides valuable insights into the association between CT values, clinical characteristics, and laboratory findings in hospitalized COVID-19 patients. The findings underscore the importance of CT values in assessing disease severity and potential prognostication. Further research is warranted to validate these findings in larger and more diverse patient populations.